Characterization of a transitional preplasmablast population in the process of human B cell to plasma cell differentiation - Jourdan, Michel; Caraux, Anouk; Caron, Gersende; Robert, Nicolas; Fiol, Geneviève; Rème, Thierry; Bolloré, Karine; Vendrell, Jean-Pierre; Gallou, Simon Le; Mourcin, Frédéric; Vos, John De; Kassambara, Alboukadel; et al. (The journal of immunology, 2011)
The early steps of differentiation of human B cells into plasma cells are poorly known. We report a transitional population of CD20low/−CD38− preplasmablasts along differentiation of human memory B cells into plasma cells in vitro. Preplasmablasts lack documented B cell or plasma cell (CD20, CD38, and CD138) markers, express CD30 and IL-6R, and secrete Igs at a weaker level than do plasmablasts or plasma cells. These preplasmablasts further differentiate into CD20−CD38highCD138− plasmablasts and then CD20−CD38highCD138+ plasma cells. Preplasmablasts were fully characterized in terms of whole genome transcriptome profiling and phenotype. Preplasmablasts coexpress B and plasma cell transcription factors, but at a reduced level compared with B cells, plasmablasts, or plasma cells. They express the unspliced form of XBP1 mRNA mainly, whereas plasmablasts and plasma cells express essentially the spliced form. An in vivo counterpart (CD19+CD20low/−CD38−IL-6R+ cells) of in vitro-generated preplasmablasts could be detected in human lymph nodes (0.06% of CD19+ cells) and tonsils (0.05% of CD19+ cells). An open access “B to Plasma Cell Atlas,” which makes it possible to interrogate gene expression in the process of B cell to plasma cell differentiation, is provided. Taken together, our findings show the existence of a transitional preplasmablast population using an in vitro model of plasma cell generation and of its in vivo counterpart in various lymphoid tissues.
Gesehen am 05.07.2022